2016
DOI: 10.1177/0011000015621149
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Attitudes of United Arab Emirates Students

Abstract: The psychological help-seeking patterns of college students in the United Arab Emirates (UAE) have only recently begun to be examined. Initial suggestions indicate that the majority of Emirati students treat help seeking from counselors as a last resort, which may be linked to aspects of Emirati culture including feared loss of societal face, stigma associated with seeking help, and discouragement of self-disclosure to individuals outside of the family. The relationship among fear of losing face, stigma, self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 50 publications
(162 reference statements)
2
26
0
1
Order By: Relevance
“…Only two biases appeared worthy of further investigation, one being gender related and the other concerning a difference in opinion about their national politics. Some research in this field hypothesizes that, within the Arab culture, there is a clear preference to and acceptability of females as therapists (24, 41). At this point, it is important to take into consideration our unique sample size, of which the majority are women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two biases appeared worthy of further investigation, one being gender related and the other concerning a difference in opinion about their national politics. Some research in this field hypothesizes that, within the Arab culture, there is a clear preference to and acceptability of females as therapists (24, 41). At this point, it is important to take into consideration our unique sample size, of which the majority are women.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is important to take into consideration our unique sample size, of which the majority are women. Regarding gender preferences in clinicians, women may feel more comfortable with a female therapist or medical doctor, so that they can address gender-related issues more openly and with greater ease (41). Furthermore, in the Arab world, studies have reported that, as a part of cultural norms, women are often assigned a caretaker role that is expected to nurture and care for others (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the study's strengths was that the participants were mature adults who had accessed and maintained long term counselling for help with psychological problems. This provides a useful contrast to the majority of research on Muslim help-seeking which is conducted with university students and based on the hypothetical experience of distress and help-seeking (see, for example, Al-Adawi et al, 2002;Al-Krenawi et al, 2000, 2009Alajlan, 2016;Heath et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other faith-based explanatory models instead construct mental health distress as an act of God, regarded either as divine punsihment for sinfulness or weakness in faith or as a divine testing of the personal fortitude or strength of faith of the person suffering (Aloud & Rathur, 2009;Heath et al, 2016;Padela et al, 2011;Scull et al, 2014). Such beliefs are likely to bolster coping strategies focused on self-reliance and non-disclosure and in turn, according to Fakhr El-Islam (2008) may augment fears of stigma and public shame.…”
Section: Explanatory Modelsmentioning
confidence: 99%
“…Araştırmacılar, saygınlığını yitirme kaygısını önemli kültürel değişkenlerden biri olarak görmekte ve son yıllarda, saygınlığını yitirme kaygısının öncülleri, saygınlığını yitirme kaygısıyla ilişkili değişkenler ve saygınlığını yitirme kaygısının sonuçlarıyla ilgili çok sayıda araştırma gerçekleştirmektedirler (David, 2010;Heath, Vogel ve Al-Darmaki, 2016;Leong, Byrne, Hardin, Zhang ve Chong, 2018;Leong vd., 2011;Mak ve Chen, 2006;Topkaya, 2015a;Topkaya, Şahin ve Gençoğlu, 2019;Tuliao, Velasquez, Bello ve Pinson, 2016). Gerçekleştirilen araştırmalar yüksek düzeyde saygınlığını yitirme kaygısının bir dizi olumsuz ruh Nursel Topkaya -Ertuğrul Şahin -Cem Gençoğlu sağlığı göstergesiyle ilişkili olduğunu göstermektedir.…”
unclassified